HUBUNGAN PEMENUHAN KEBUTUHAN DASAR BALITA (ASUH, ASAH, DAN ASIH) DENGAN PERKEMBANGAN BALITA YANG BERSTATUS BGM (BAWAH GARIS MERAH) DI DESA SUKOJEMBER KECAMATAN JELBUK KABUPATEN JEMBER - Arifah, Nurul; Rahmawati, Iis; Dewi, Erti I. (FKM - UNEJ, 2013)
Under-five childrenâs development are influenced by parenting style. In malnutritioned children (under-red-line children), parenting style especially in fullfilling their basic needs influenced childrenâs growth and development. The objective of this study is to analyze the correlation of under-five childrenâs basic needs (foster, hone, and compassion) fullfillment with malnutritioned childrenâs development in Sukojember Village, Jelbuk Sub-District, Jember. This study was a cross sectional study with 28 samples acquired by total sampling method. Data were collected by using measure instrument of the study contained basic needs fullfillment questionnaire and developmental measurement for under-five children. Simple linear regression test was used toÂ analyze data with the p value of 0.005 which is under Î± value (0.05). The coefficient of determination is 0.268 with r values of 0.519. this means there is a significant correlation between the variables. The result proved there is a correlation between malnutrioned under-five childrenâs development with their basic needs fulfillment. The recommendation of this study for the next researcher is to analyze which under-five childrenâs basic needs affect their development most. Keywords: basic needs, development, Malnutritioned-red-line